Bronchopleurocutaneous Fistula: A Rare Complication of Pulmonary Tuberculosis - José Montez, Ana Sofia (2015)
Introduction: Multiple complications can occur in tuberculosis. Bronchopleurocutaneous fistula is a pathological communication between bronchus, pleural space and skin.Clinical Case: We present a 47 year-old male patient, schizophrenic, who presented with complaints of pleuritic chest pain, cough and weight loss. The patient was cachectic with purulent drainage from an orifice in the antero-lateral left chest wall. In this drainage acidfast bacilli were identified and chest radiograph showed bilateral infiltrates. He was admitted to the Infectious Diseases Department with the diagnosis of fistulized pulmonary tuberculosis, confirmed by visualization of acid-fast bacilli, positive polymerase chain reaction and cultures for Mycobacterium tuberculosis in the sputum. The patient was started on quadruple antituberculosis therapy and had afavorable outcome.Conclusions: Bronchopleurocutaneous fistula is a rare complication of pulmonary tuberculosis. Despite pulmonary tuberculosis being a common condition in our country, the rarity of this complication prompted the authors to present it.